Comparative Study of Public Administration in the UK and Australia: Studi Perbandingan Administrasi Publik di Inggris dan Australia - Pratama, Angga Ariesandy Putra; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2025)
Background: Comparative analysis in public administration provides a broader understanding of governance systems across nations. Specific Background: This study explores administrative structures and practices in the United Kingdom and Australia, two countries that share a historical connection yet implement distinct administrative systems. Knowledge Gap: Previous research has generally focused on single-country governance without a structured comparison highlighting administrative efficiency and decentralization. Aim: This study aims to analyze and compare the core characteristics of public administration in both nations. Results: The findings show that while the UK applies a centralized parliamentary system, Australia adopts a federal approach that emphasizes state autonomy. Novelty: The research offers a new perspective by linking theoretical aspects of public administration with practical differences between two developed democratic systems. Implications: The study provides insights that can serve as a reference for improving administrative governance and decentralization models in other countries, including Indonesia. Highlights:• Comparison of administrative systems between the UK and Australia• Centralized versus federal governance structures• Lessons for administrative reform and decentralization Keywords: Public Administration, Comparative Study, Governance, United Kingdom, Australia